2017
DOI: 10.1111/head.13158
|View full text |Cite
|
Sign up to set email alerts
|

Supratrochlear Neuralgia: A Prospective Case Series of 15 Patients

Abstract: Supratrochlear neuralgia is an uncommon disorder causing pain in the medial region of the forehead. It may be differentiated from supraorbital neuralgia and other similar headaches and neuralgias based on the topography of the pain and the response to anesthetic blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…To our knowledge, this is the first report of trigeminal nerve branch blocks as a treatment for chronic ocular pain. However, several studies have reported the use of separate supraorbital, supratrochlear, infraorbital, and infratrochlear nerve blocks for the treatment of migraine headaches, supratrochlear neuralgia, infraorbital neuralgia, and lacrimal neuralgia 19, 20, 21, 22. The majority of patients who underwent these peripheral nerve injections had several months of pain relief with no noted complications.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of trigeminal nerve branch blocks as a treatment for chronic ocular pain. However, several studies have reported the use of separate supraorbital, supratrochlear, infraorbital, and infratrochlear nerve blocks for the treatment of migraine headaches, supratrochlear neuralgia, infraorbital neuralgia, and lacrimal neuralgia 19, 20, 21, 22. The majority of patients who underwent these peripheral nerve injections had several months of pain relief with no noted complications.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline pain generally follows nerve topography involving the forehead, eyebrow and internal angle of the orbit that is constant with exacerbations experienced transiently as severe pain with a sharp, shock-like quality. Pain can be elicited with pressure at the supraorbital notch (supraorbital) (43), medial third of supraorbital rim (supratrochlear) (44), or internal angle of the orbit above medial canthus (infratrochlear) (45). A key difference from trochleodynia is lack of pain exacerbation with vertical eye movements or ophthalmoplegia.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…One neuralgia that is linked to the V1 branch, is supraorbital neuralgia, characterized by persistent pain over the supraorbital region and medial region forehead [119]. It may be differentiated from supratrochlear neuralgia based on the topography of the pain, which can be confirmed with anaesthetic blockade [120]. Lacrimal neuralgia, is pain localized to the orbital and periorbital area, and was first described in 2013 [121].…”
Section: Other Painful Conditionals Of the Trigeminal Nerve Branchesmentioning
confidence: 99%